Relapse and its mitigation: Toward behavioral inoculation. Issue 2 (30th January 2023) - Kimball, Ryan T.; Greer, Brian D.; Fuhrman, Ashley M.; Lambert, Joseph M.
Abstract: Relapse following the successful treatment of problem behavior can increase the likelihood of injury and the need for more intensive care. Current research offers some predictions of how treatment procedures may contribute to relapse, and conversely, how the risk of relapse can be mitigated. This review describes relapse‐mitigation procedures with varying levels of support, the quantitative models that have influenced the research on relapse mitigation, different experimental methods for measuring relapse mitigation, and directions for future research. We propose that by viewing the implementation of relapse‐mitigation procedures as a means of producing behavioral inoculation, clinicians are placed in the proactive and intentional role of exposing their client's behavior to an array of reinforcement and stimulus conditions during treatment with the goal of decreasing the detrimental impact of future treatment challenges.